Fetal outcomes and associated factors of antepartum hemorrhage in Ethiopia: A systematic review and meta-analysis - Gemeda Wakgari Kitil; Adamu Ambachew Shibabaw; Eyob Getachew; Amlaku Nigusie Yirsaw; Berihun Agegn Mengistie; Gebeyehu Lakew; Gebrehiwot Berie Mekonnen; Solomon Seyife Alemu; Firomsa Bekele; Lema Fikadu Wedajo; Addisalem Workie Demsash; Wubishet Gezimu; et al. (PLoS ONE, 2025)
Background Antepartum hemorrhage (APH) is a significant obstetric complication characterized by bleeding from the genital tract before the onset of labor. It poses serious risks to both maternal and fetal health, with potential outcomes including preterm birth, low birth weight, and increased perinatal mortality. In Ethiopia, where access to comprehensive prenatal care and emergency obstetric services may be limited, the impact of APH on fetal outcomes is a pressing concern. Despite the gravity of this condition, there is a lack of synthesized evidence on its prevalence and the associated risk factors specific to the Ethiopian context. This systematic review and meta-analysis aim to consolidate existing research on the fetal outcomes of APH and identify the key factors contributing to its incidence and severity in Ethiopia. Methods Following the PRISMA checklist guidelines, this study concentrated on research undertaken in Ethiopia. Comprehensive searches across multiple databases Google Scholar, Google, Web of Science, and PubMed yielded six pertinent studies. Data were systematically gathered using a structured checklist and analyzed with STATA version 14. The Cochrane Q test and the I² statistic were utilized to assess heterogeneity. Additionally, publication bias was examined using Egger’s weighted regression, a funnel plot, and Begg’s test. Results This study reviewed 525 research articles that included a total of 22,914 participants. Our meta-analysis revealed that the pooled prevalence of perinatal mortality due to antepartum hemorrhage in Ethiopia is 21.79% (95% CI: 12.32–31.25). Key factors influencing perinatal mortality associated with antepartum hemorrhage included living in rural areas (OR =  1.62, 95% CI: 1.33–1.98), delays in seeking medical care for over 12 hours (OR =  5.43, 95% CI: 1.01–29.14), prematurity (OR =  9.00, 95% CI: 5.39–15.03), and experiencing severe vaginal bleeding prior to arrival at a medical facility (OR =  7.04, 95% CI: 2.14–23.13). Conclusion The study reveals a high perinatal mortality rate of 21.79% associated with antepartum hemorrhage in Ethiopia. Contributing factors include rural residence, delays in seeking care, prematurity, and severe vaginal bleeding. To reduce mortality, improve rural healthcare, strengthen emergency systems, and enhance prenatal care. Public education on early intervention and specialized care for premature infants are also essential. Collaboration among healthcare providers, government, and NGOs is crucial for effective, sustainable solutions.